An unusual complication of nasal foreign body in a pediatric patient: A case report - Swain, Santosh Kumar; Sahu, Mahesh Chandra (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Foreign body (FB) of nasal cavity is a common clinical incidence in Pediatric Otorhinola-ryngology. Inferior meatus is a rare location for FB lodgment inside the nasal cavity. In case of nasal FB, patients usually present with nasal obstruction, foul smell discharge and epistaxis. FB at the inferior meatus blocking the nasolacrimal outflow is an extremely rare complication of nasal FB leading to dacryocystitis. X-ray skull will help to rule out the radio-opaque FB in the nasal cavity. Diagnostic nasal endoscopy will help for accurate diagnosis of nasal FB. Early diagnosis and safe removal of FB from nasal cavity help to reduce complications. We present an unusual case of nasal FB in a 10-year-old boy presented with chronic dacryocystitis. Chronic dacryocystitis is an extremely rare presentation due to FB of nasal cavity.